The Effect of Motivation, Work Environment and Transformational Leadership Style on Employees Performance with New Normal Conditions through Job Satisfaction as Intervening Variable at Bank Indonesia Jember - Biondi Prasadha Priyadhana; Sri Wahyu Lely Hana; Imam Suroso (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to examine and analyze motivation, work environment and transformational leadership style on employee performance through job satisfaction of KPwBI Jember employees. The data used in this study are primary data. The data processing method uses the Partial Least Square analysis method with the help of the PLS Smart analysis tool. The results showed that motivation had a significant effect on employee satisfaction work environment had no significant effect on job satisfaction, transformational leadership style had no significant effect on job satisfaction, motivation had a significant effect on work performance, work environment had no significant effect on employee performance, and transformational leadership style did not significant effect on employee performance.